2021
DOI: 10.21203/rs.3.rs-185898/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Azithromycin Concentrations During Long-Term Regimen in Patients With MALT Lymphoma

Abstract: IntroductionIn view of the antineoplastic effects of the macrolide clarithromycin in mucosa associated lymphatic tissue (MALT)-lymphoma, we performed a pilot study assessing levels of azithromycin in plasma, peripheral blood mononuclear cells (PBMC) and polymorphonuclear leukocytes (PMN) of MALT-lymphoma patients to determine the pharmacokinetics and potential influences of respective concentrations on the therapeutic outcome.Material and methodsIn total 16 patients with MALT-lymphoma received 1.5g of oral azi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…However, among 16 patients receiving azithromycin (2 with gastric and 14 with extragastric MALT lymphoma), two patients achieved CR, and two had PR (25% ORR) [ 116 ]. Furthermore, Scheibenpflug et al reported that among the 16 patients with MALT lymphoma, high intracellular concentrations of azithromycin in peripheral blood mononuclear cells were not associated with the responsiveness to azithromycin, but intracellular concentrations of azithromycin in polymorphonuclear leukocytes correlated with poor responsiveness [ 117 ].…”
Section: Clinical Efficacy Of Immunomodulatory Agents For Hp-negative...mentioning
confidence: 99%
“…However, among 16 patients receiving azithromycin (2 with gastric and 14 with extragastric MALT lymphoma), two patients achieved CR, and two had PR (25% ORR) [ 116 ]. Furthermore, Scheibenpflug et al reported that among the 16 patients with MALT lymphoma, high intracellular concentrations of azithromycin in peripheral blood mononuclear cells were not associated with the responsiveness to azithromycin, but intracellular concentrations of azithromycin in polymorphonuclear leukocytes correlated with poor responsiveness [ 117 ].…”
Section: Clinical Efficacy Of Immunomodulatory Agents For Hp-negative...mentioning
confidence: 99%
“…Moreover, the drug accumulates in the macrophages and polymorphonuclear leucocytes (up to 200 times the serum concentration) and supports their activity against infections 9,10 . This efficacy lasts for several days because of the long azithromycin half‐life of 68–79 hours 1,11 . On multiple dosing, the half‐life of azithromycin in the tissues and the tissue to serum concentration ratio increase 9 .…”
mentioning
confidence: 91%
“…Conversely, its release from tissues is quite slow. 6,[9][10][11] Following an oral administration of a single dose of 500 mg, the tissue concentrations of azithromycin can reach over 100-fold the serum concentrations, especially in tonsil, lymph nodes, liver, lung, and prostate tissues. The significantly high tissue concentrations would overcome the minimum inhibitory concentration of 90% of pathogens (MIC90).…”
mentioning
confidence: 99%
See 2 more Smart Citations